Redescription of a poorly known epialtid crab Pugettia pellucens Rathbun, 1932 (Crustacea: Decapoda: Brachyura: Majoidea) and description of a new species from Sagami Bay, Japan - Ohtsuchi, Naoya; Kawamura, Tomohiko; Takeda, Masatsune (Zootaxa, 2014)
A poorly known epialtid crab species, Pugettia pellucens Rathbun, 1932, is redescribed and a closely allied new species P. vulgaris n. sp. is described and illustrated on the basis of material from Sagami Bay, Japan. Pugettia pellucens was originally described as a subspecies of P. quadridens (De Haan, 1839), but it is confirmed that the taxon is distinct from P. quadridens. The superficially similar Pugettia vulgaris n. sp. can be distinguished from P. pellucens by several morphological characters. The new species is also similar to P. elongata Yokoya, 1933, and P. intermedia Sakai, 1938, but can also be separated by various carapace and gonopodal characters.